Iron-Sulfur Clusters in Chemistry and Biology. - Rouault, Tracey A. (De Gruyter, 2014)
This volume on iron-sulfur clusters includes chapters that cover the history of the discovery of iron-sulfur clusters in the 1960s to discoveries of their role in the enzyme, aconitase (1980s), and numerous other proteins. It explains basic chemistry principles, how microbes, plants, and animals synthesize these complex prosthetic groups, and why it is important to understand the chemistry and biogenesis of FeS proteins.